Overview of Resilience in High School Students - Yosep, Iyus; Mardhiyah, Ai; Maulana, Indra; Lukman, Mamat; Hikmat, Rohman (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aim: This study aims to determine the description of resilience in students at Bandung High School. Method: This study used a descriptive design with purposive sampling technique, involving 100 respondents consisting of students from grades X to XII aged 12 to 19 years. Data were collected using the Connor-Davidson Resilience Scale (CD-RISC), which consists of 25 statements with a score range of 0-100. The results of the validity and reliability tests showed that the instruments used were valid and reliable. Results: The results showed that 30% of respondents had a high level of resilience (30 students), 42% were at a moderate level of resilience (42 students), and 28% had low resilience (28 students). The average resilience score was 60.94, with a score range between 35 and 100. These findings indicate the need for special attention to students with low resilience, who are at risk for psychological problems such as anxiety and depression. Social support, coping skills, and specially designed intervention programs can help improve resilience among students. Conclusion: This study underscores the importance of understanding high school students’ resilience levels to support their mental and academic well-being. More effective support programs for students with low resilience are needed, as well as further research to explore factors that influence resilience.